Data from: Persistent near real-time passive acoustic monitoring for baleen whales from a moored buoy: system description and evaluation ... - Baumgartner, Mark F.; Bonnell, Julianne; Van Parijs, Sofie M.; Corkeron, Peter J.; Hotchkin, Cara; Ball, Keenan; Pelletier, Léo-Paul; Partan, Jim; Peters, Don; Kemp, John; Pietro, Jeff; Newhall, Kris; et al. (Dryad, 2019)
1. Managing interactions between human activities and marine mammals often relies on an understanding of the real-time distribution or occurrence of animals. Visual surveys typically cannot provide persistent monitoring because of expense and weather limitations, and while passive acoustic recorders can monitor continuously, the data they collect are often not accessible until the recorder is recovered. 2. We have developed a moored passive acoustic monitoring system that provides near real-time occurrence estimates for humpback, sei, fin, and North Atlantic right whales from a single site for a year, and makes those occurrence estimates available via a publicly accessible website, email and text messages, a smartphone/tablet app, and the U.S. Coast Guard’s maritime domain awareness software. We evaluated this system using a buoy deployed off the coast of Massachusetts during 2015-2016 and redeployed again during 2016-2017. Near real-time estimates of whale occurrence were compared to simultaneously ... : READMEDescription of all data files in this datasetmanual_analysis_nomans0315_realtimeNear real-time whale occurrence estimates for the 2015-2016 DMON/LFDCS buoymanual_analysis_nomans0916Near real-time whale occurrence estimates for 2016-2017 DMON/LFDCS buoytally_periods_manual_nomans0315_correctedAudio analysis of species occurrence for 2015-2016 DMON/LFDCS buoyaerialAerial survey results for flights conducted by the New England Aquarium (NEAq) and NOAA Northeast Fisheries Science Center ...